2016
DOI: 10.1109/tcomm.2015.2500234
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Near-Capacity Protograph LDPC Code Sequences With Block-Error Thresholds

Abstract: Density evolution for protograph Low-Density Parity-Check (LDPC) codes is considered, and it is shown that the message-error rate falls double-exponentially with iterations whenever the degree-2 subgraph of the protograph is cyclefree and noise level is below threshold. Conditions for stability of protograph density evolution are established and related to the structure of the protograph. Using large-girth graphs, sequences of protograph LDPC codes with block-error threshold equal to bit-error threshold and bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 34 publications
(67 reference statements)
0
27
0
Order By: Relevance
“…This can be proved by contradiction. For details of the proof, we refer readers to [6,Theorem 1]. So, we have shown that…”
Section: ) Proof Of Theoremmentioning
confidence: 85%
See 3 more Smart Citations
“…This can be proved by contradiction. For details of the proof, we refer readers to [6,Theorem 1]. So, we have shown that…”
Section: ) Proof Of Theoremmentioning
confidence: 85%
“…Block-error threshold of protograph ensemble is defined as the supremum of the set of ǫ for which probability of block error, denoted by P B , tends to zero as the number of iterations tends to infinity. In [6], sufficient conditions for block-error threshold being equal to bit-error threshold have been derived using the following two steps:…”
Section: Block-error Threshold Extensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Density evolution (DE) and protograph EXIT (PEXIT) techniques are known to facilitate protograph design, typically resulting in the Multi Edge Type (MET) protographs, in which parallel edges are allowed [5]- [10]. MET protograph ensembles have been shown to achieve capacityapproaching thresholds [5], with DE-based optimization enabling to design small-sized protographs, for which the derived LDPC codes are asymptotically close to the capacity for BEC and BIAWGN channels [6]. Numerous other work focus on applications for other channels and specific processing models.…”
Section: Introductionmentioning
confidence: 99%